2018
DOI: 10.3389/fneur.2018.00892
|View full text |Cite
|
Sign up to set email alerts
|

Errors of Upright Perception in Patients With Vestibular Migraine

Abstract: Patients with vestibular migraine (VM) often report dizziness with changes in the head or body position. Such symptoms raise the possibility of dysfunction in neural mechanisms underlying spatial orientation in these patients. Here we addressed this issue by investigating the effect of static head tilts on errors of upright perception in a group of 27 VM patients in comparison with a group of 27 healthy controls. Perception of upright was measured in a dark room using a subjective visual vertical (SVV) paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
0
30
1
1
Order By: Relevance
“…Further molecular, imaging, and neurophysiological studies are needed to better define the pathogenic signatures of vestibular migraine. Better understanding of symptoms related to visuo-vestibular integration in VM, such as tilt sensitivity, upright misperception [29], and ictal nystagmus Box 1 Bárány Society diagnostic criteria for persistent postural perceptual dizziness (A) One or more symptoms of dizziness, unsteadiness or non-spinning vertigo on most days for at least 3 months Symptoms last for prolonged (hours-long) periods of time, but may wax and wane in severity Symptoms need not be present continuously throughout the entire day (B) Persistent symptoms occur without specific provocation, but are exacerbated by three factors: upright posture, active or passive motion without regard to direction or position, and exposure to moving visual stimuli or complex visual patterns (C) The disorder is triggered by events that cause vertigo, unsteadiness, dizziness, or problems with balance, including acute, episodic or chronic vestibular syndromes, other neurological or medical illnesses, and psychological distress When triggered by an acute or episodic precipitant, symptoms settle into the pattern of criterion A as the precipitant resolves, but may occur intermittently at first, and then consolidate into a persistent course When triggered by a chronic precipitant, symptoms may develop slowly at first and worsen gradually (D) Symptoms cause significant distress or functional impairment (E) Symptoms are not better accounted for by another disease or disorder [21] may provide further pathophysiological clues to this condition.…”
Section: Vestibular Migrainementioning
confidence: 99%
“…Further molecular, imaging, and neurophysiological studies are needed to better define the pathogenic signatures of vestibular migraine. Better understanding of symptoms related to visuo-vestibular integration in VM, such as tilt sensitivity, upright misperception [29], and ictal nystagmus Box 1 Bárány Society diagnostic criteria for persistent postural perceptual dizziness (A) One or more symptoms of dizziness, unsteadiness or non-spinning vertigo on most days for at least 3 months Symptoms last for prolonged (hours-long) periods of time, but may wax and wane in severity Symptoms need not be present continuously throughout the entire day (B) Persistent symptoms occur without specific provocation, but are exacerbated by three factors: upright posture, active or passive motion without regard to direction or position, and exposure to moving visual stimuli or complex visual patterns (C) The disorder is triggered by events that cause vertigo, unsteadiness, dizziness, or problems with balance, including acute, episodic or chronic vestibular syndromes, other neurological or medical illnesses, and psychological distress When triggered by an acute or episodic precipitant, symptoms settle into the pattern of criterion A as the precipitant resolves, but may occur intermittently at first, and then consolidate into a persistent course When triggered by a chronic precipitant, symptoms may develop slowly at first and worsen gradually (D) Symptoms cause significant distress or functional impairment (E) Symptoms are not better accounted for by another disease or disorder [21] may provide further pathophysiological clues to this condition.…”
Section: Vestibular Migrainementioning
confidence: 99%
“…Figure 2 shows the number of records removed and the reasons for exclusion. Finally, seven studies [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ] were included in the present review.…”
Section: Resultsmentioning
confidence: 99%
“…The seven studies included in this review comprised 10 samples with 10 independent comparisons providing data from 816 participants (34% males and 66% females). The seven studies [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ] had eight independent comparisons, including 669 patients with migraine (mean age of 36.72 ± 4.9 years old); two of the studies [ 52 , 56 ] had two independent comparisons with reported data for 147 subjects with TTH (mean age of 39.52 ± 6.81 years old). The exposed group incorporated patients with migraine and TTH, and 364 healthy subjects formed the non-exposed group (mean age 35.87 ± 5.81 years old).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations